L’enjeu des années 1990 : la police, les tribunaux et les municipalités - Waller, Irvin (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1990)
This article looks at the 1990's agenda for Québec to improve the protection for victims of crime.It summarises the progress made by Québec in implementing the United Nations Declaration on Victim Rights. It compares the progress in Québec with other provinces and countries.It examines how police leadership to implement procedures that respect victims of crime could help the police, while improving significantly respect for victims. It discusses how Québec could combine the civil and criminal interests of victims of crime, while reducing court backlogs. It stresses the importance of reducing victimisation by building on the Agenda for Safer Cities developed in Montréal in 1989. It also calls for more comparative research on the extent to which reforms in different jurisdictions are meeting the needs of crime victims.